ANALISIS RISIKO KONSTRUKSI PADA PEKERJAAN PEMBANGUNAN JARINGAN & GARDU DISTRIBUSI 865 kVA PT CHAROEN POKHPAND FARM CIGEULIS - Muhammad Anang Kusumo; Eri Setia Romadhon (FTSP Universitas Jayabaya, 2022)
Electrical energy is one of the main components which includes the most important infrastructure in life today. Currently, the distribution of electrical energy in Indonesia has reached 99.45% in the fourth quarter of 2021. The current availability of electrical energy is not in line with the growth in electricity consumption by consumers, resulting in a surplus of 46.8% in electricity consumption. Java and Bali Islands. One of the efforts to optimize the existing electrical energy is to meet the demand for electricity in the livestock industry sector in the Banten region owned by PT Charoen Pokhpand Farm Cigeulis with a demand for electricity of 865 kVA. In the process of constructing and developing a power distribution system for industrial customers, there are many risks that may arise both during the construction and operation phases. One possible solution is to carry out a risk analysis that may occur in the construction of the 865 kVA distribution network and substation of PT Charoen Pokhpand Farm Cigeulis. Risk analysis begins with identifying risks using the brainstorming method or interviews with questionnaire media. At the risk analysis stage, the Failure Mode and Effect Analysis (FMEA) method was used and supported by distributing questionnaires. Based on the results of the analysis of the 4 existing targets, 30 risks are relevant to this development work and 18 risks are dominant in terms of cost and time. From the results of the risk analysis, there are risks that have extreme levels that impact on costs and time, namely the risk of work accidents occurring in the work of planting poles and withdrawing SUTM, excavation work and laying SKTM cables, as well as construction of distribution substations with preventive plans that can be carried out is to ensure the fulfillment of K3 standards by the Executor according to what is stated in the Contract, carry out safety briefing before work is carried out, and appoint K3 supervisors from the implementing party and PT PLN (Persero).